Genotypic Diversity of the Wheat leaf blotch pathogen (Septoria tritici) in Buenos Aires Province - Cordo, Cristina Alicia (2006)
The population structure and genotypic diversity of Septoria tritici Rob ex Desm. from two crop field populations in Buenos Aires Province were studied with DNA restriction fragment length polymorphism. Hierarchical samples were taken from different cultivars. A total of 120 single spore isolates was subject to molecular analysis to compare the genetic structure of Los Hornos and Balcarce populations separated by 500km. Eight RFLP loci and 1DNA fingerprinting were used. Among the total of the isolates, 24 RFLP alleles were detected from the first population and 22 from the second. Gene and genotype diversity were high in both populations. Different haplotypes for each region were identified. Identical haplotypes were clustered in the same location in the field. The mean gene diversity and the mean genotypic diversity were high for the 8 loci of RFLP. This means that Balcarce and Los Hornos were significantly different. The X2 was significant (P>0.005) only for two RFLP locus, then both populations were not independant. They had to be compared with an European and an American populations. Balcarce population was very different to all of them. Both Argentine populations were very similar at regional level but strongly different at a continental level. The greatest genetic variability between continents belonged to Argentine population. The amount of gene flow was high when all the populations were compared.